Política, vida cívica e religião: uma análise das memórias de Eneias no livro III da Eneida de Virgílio (séc. I a.C.) - Filgueira, Ana Paula Santana (2016)
The Aeneid, an epic poem written by Publius Vergilius Maro, is dated 19 a. C. This epic tells the route taken by survivors of the Trojan War, led by Aeneas hero, in search of a promised land of the gods, to found a new city. In this research, we take as an object of study Book III of the Aeneid in which Aeneas character tells how was the course of his first years of exile, always arriving and departing spaces where he went through experiences that shaped his personality as political leader, military and religious, and influenced their travel companions. We carry out a reflection on how these characteristics aggregated to Aeneas figure can help us in thinking about politics, civic life and religion of Rome, during the period in which the epic Virgilian was produced, covering the government of Octavian Augustus, 14 to . C. and 27 d. C. promote an analysis of mythos, memory and space, identifying how the Trojans exiles in Aeneid is recognized and interact with the spaces in which landed in particular Thrace, Delos, Crete, Estrofádas islands, Buthrotum, Italy and Drepano, aiming to demonstrate how a literary source may suggest cultural elements of the society that produced it.